2017
DOI: 10.1007/s00266-017-1013-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foam Wound Dressing Technique for Areola Skin Graft Stabilization and Nipple Protection After Nipple–Areola Reconstruction

Abstract: We describe a new wound management technique using a soft dressing material to stabilize the areola skin graft and protect the nipple after nipple-areola reconstruction at the final stage of breast reconstruction. We introduced a center-fenestrated multilayered hydrocellular polyurethane foam dressing material that provides adequate pressure and retains a moist environment for a smooth skin graft "take." Moreover, the reconstructed nipple can be monitored at any time through the fenestrated window for adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The aim of the study was to test if the addition of multilayered hydrocellular polyurethane foam dressing could help achieve post-surgical healing through the mechanisms of (1) applying adequate pressure to the nipple and (2) maintaining a moist wound environment. In this study, areola skin grafts following reconstructive breast surgery demonstrated improved clinical outcomes with the addition of the multilayered hydrocellular polyurethane foam dressings [44].…”
Section: Other Indicationsmentioning
confidence: 84%
“…The aim of the study was to test if the addition of multilayered hydrocellular polyurethane foam dressing could help achieve post-surgical healing through the mechanisms of (1) applying adequate pressure to the nipple and (2) maintaining a moist wound environment. In this study, areola skin grafts following reconstructive breast surgery demonstrated improved clinical outcomes with the addition of the multilayered hydrocellular polyurethane foam dressings [44].…”
Section: Other Indicationsmentioning
confidence: 84%
“…A foam sponge secured by staples is an alternative technique for securing small- to medium-sized grafts, helping to distribute pressure more evenly 23,24 . Reston polyurethane foam was proposed as a bolster in 1984 25 and has been described across multiple anatomical sites: limbs, breasts, the penis, the face, and oral cavity 26–28 . In an RCT of 106 patients with SSG secured by sponge versus 106 receiving TOB in anatomically challenging areas such as the nose and ear, sponge fixation was associated with fewer complications, shorter operating times, and a success rate of 97.1% compared with 89.6%, although this did not reach statistical significance 18 .…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Reston polyurethane foam was proposed as a bolster in 1984 25 and has been described across multiple anatomical sites: limbs, breasts, the penis, the face, and oral cavity. [26][27][28] In an RCT of 106 patients with SSG secured by sponge versus 106 receiving TOB in anatomically challenging areas such as the nose and ear, sponge fixation was associated with fewer complications, shorter operating times, and a success rate of 97.1% compared with 89.6%, although this did not reach statistical significance. 18 Risk of bias was high as this trial was not blind and did not define its randomization protocol.…”
Section: Tie-over Bolster Compared With No Tobmentioning
confidence: 99%
“…The main chain of polyurethane is composed of soft and hard segments. Due to the thermodynamic incompatibility between the soft and hard segments, the performance of polyurethane is related to the chemical structure and proportion of the soft and hard segments, which further affects the performance of polyurethane dressing materials [13][14][15][16][17][18]. Conventional textile fiber wound dressings usually become infiltrated with wound secretions and newly formed soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In the early days, modern dressings composed of polyurethane polymers were reported to be more effective, comfortable, convenient, and economical compared to other traditional dressings. The advantages of polyurethane dressings have played an important role in outpatient settings and inpatient care [13][14][15][16][17][18]. However, drawbacks such as the inability to control leakage, increased cost of care, and poor cost-effectiveness of polyurethane polymer-related dressings have also been reported [16,19,20].…”
Section: Introductionmentioning
confidence: 99%